The Acculturation of Building Facade Characters in Loji Wetan Area, Surakarta - Putri, Dewi Widowati; Widyastuti, Dyah Titisari (Universitas Negeri Yogyakarta, 2024)
Loji Wetan is a former European ethnic residential area to the east of Vastenburg fort, Surakarta. This area has the characteristics of European building. However, the visual are gradually fading due to changes in facade form. The research identified the character of 22 residential buildings based on variables and indicators regarding facade components which discuss roof components, columns, doors, windows, guardrails, porches or verandas, and stairs, as well as architectural facade composition which discusses symmetry, geometry, proportion and scale, rhythm, and contrast. The research show that the characteristics at Loji Wetan are a product of acculturation between colonial, Javanese and Chinese architecture. Colonial elements presented with clipped gable roofs, supporting column structures, size of the doors and window, as well as the presence of a 2-story building. Javanese influence the presence of carved ornaments above lintels, wooden lattice window models, wooden columns, and the symmetry of the faí§ade which represent the Javanese philosophy of balance. Meanwhile, the Chinese style is shown through the column-free facade that squeezes into the street. This product of acculturation influenced by several factors, including socio-cultural, political, and economic factors.